Kinetic parameters estimation for increasing the efficiency of nutrient absorption in fruit trees - Paula, Betania Vahl De; Rozane, Danilo Eduardo [UNESP]; Melo, George Welligton Bastos De; Natale, William; Marques, Anderson Cesar Ramos; Brunetto, Gustavo (Sociedade Brasileira de Fruticultura, 2021)
The selection of rootstocks presenting traits of interest, such as resistance to pests and diseases, and compatibility with scion capable of producing fruits attractive to the market, has revolutionized fruit crops worldwide. However, the enormous potential of plants to be selected based on their nutrient uptake efficiency is yet to be properly explored; it can be done based on knowledge about kinetic parameters such as Influx, Maximum uptake velocity, Constant ion affinity with the carrier, and Minimum concentration. The adaptation of a methodology elaborated for annual crops to set kinetic parameters, as well as the Brazilian development of the Influx software, enabled selecting not only peach rootstocks with different nutrient uptake capacities, but also observing the influence the grafting of a particular cultivar crown has on rootstock’s ability to uptake a given nutrient from the soil. Thus, fruit tree rootstocks and cultivars can always be selected based on traits desired by fruit growers and consumers, with emphasis on yield and quality of fruits. They can also be more efficient in taking up nutrients from low natural-fertility soils that require lower nutrient amounts, a fact that increases fertilizer use rationalization and reduces environmental contamination processes resulting from excessive nutrient applications.

A seleção de porta-enxertos com características de interesse, como resistência a pragas e doenças, e compatibilidade com copa capaz de produzir frutos atrativos ao mercado, revolucionou as frutíferas em todo o mundo. No entanto, o enorme potencial das plantas de serem selecionadas com base em sua eficiência de absorção de nutrientes ainda não foi devidamente explorado; isso pode ser feito com base no conhecimento dos parâmetros cinéticos, como influxo, velocidade máxima de absorção, constante de afinidade do íon com o transportador e concentração mínima. A adaptação de uma metodologia elaborada para safras anuais, para definição de parâmetros cinéticos, bem como o desenvolvimento brasileiro do software Influx possibilitaram não só selecionar porta-enxertos de pessegueiro com diferentes capacidades de absorção de nutrientes, mas também observar a influência da enxertia de uma determinada cultivar copa na capacidade do porta-enxerto de absorver determinado nutriente do solo. Assim, porta-enxertos e cultivares de árvores frutíferas sempre podem ser selecionados com base em características desejadas pelos fruticultores e consumidores, com ênfase na produtividade e na qualidade dos frutos. Eles também podem ser mais eficientes na absorção de nutrientes de solos de baixa fertilidade natural que requerem maiores quantidades de nutrientes, fato que pode aumentar a racionalização do uso de fertilizantes e reduzir os processos de contaminação ambiental resultantes de aplicações excessivas de nutrientes.
Estimativa de parâmetros cinéticos para aumentar a eficiência da absorção de nutrientes em frutíferas
Keywords: mineral nutrition of fruit trees; fertilization; cultivars; nutrient influx; Nutrição mineral de frutíferas; adubação; cultivares; influxo de nutrientes